ANALISIS KONSENTRASI DAN PRODUKTIVITAS INDUSTRI PENGOLAHAN DAN PENGAWETAN DAGING DI INDONESIA - Jafrizal (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
This study analyzes the economies of scale, efficiency and productivity of the meat processing and preserving industry in Indonesia using the Two-Stage Data Envelopment Analysis (DEA) method and identifies the factors that influence it using the Tobit regression method. The type of data used is panel data year consisting of large and medium industry statistics from the Central Statistics Agency (BPS), Ministry of Trade, Ministry of Industry, Ministry of COMPANY, Indonesian National Meat Processor Association (NAMPA Indonesia), several libraries and previous research results , and primary data from meat processing and preserving COMPANIES in Indonesia taken by purposive sampling.